Quality Management Interconnection of Universitas Pasifik Morotai - Irawati Sabban; Irfan Hi. Abd Rahman (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2021)
The purpose of this study is to examine how interconnection practices in management, policy, planning and leadership studies are focused on quality management practices set out in the SPMI at the Universitas Pasifik Morotai (UNIPAS) Quality Assurance Institute (LPM). The research method used in this study is qualitative research. Data needed in this study are primary data and secondary data. The primary data source is the Chairperson of the Universitas Pasifik Morotai (UNIPAS) Quality Assurance Institute as Quality Control and Supervision at the Universitas Pasifik Morotai (UNIPAS). Quality documents as secondary data sources. Quality Assurance, is a proof of Universitas Pasifik Morotais commitment to develop a quality culture. The SPMI policy is a written documentation containing an outline of an explanation for understanding, designing, and implementing SPMI in the administration of higher education services to the community so that quality culture is realized. The quality management process at the Universitas Pasifik Morotai (UNIPAS) shows that the four elements of the interconnection of management studies, policy, leadership and planning have a very strong link in the administration of higher education activities at the Universitas Pasifik Morotai (UNIPAS).